Intervensi Berbasis Keperawatan Integrasi dengan Relaksasi Islami terhadap Penurunan Kecemasan dan Nyeri Pasien AMI di Ruang ICU - Angga Sugiarto; Anies Anies; Hari Peni Julianti; Mardiyono Mardiyono (Jurnal LINK, 2015)
Disease Acute Myocardial Infarction (AMI) today became one of the major causes of death (mortality) and the top 10 causes of death in the world according to the WHO. Referring to the health profile of the city, the number of patients with AMI reached 1847 people in 2010 and increased to 2130 people in 2011 with AMI Patients generally experience high anxiety associated with the disease. This study aims to determine the effect-Based Nursing Intervention Integration with relaxation Islamist in AMI patients in the ICU. The research design used in this study was a quasi-experiment with pre and post test design approach, and repeated measures that provide treatment in the 2 groups: a group given relaxation Islamist intervention and control groups. Treatment effect seen in the differences in anxiety before and after the treatment. Gauges in this study is the Numerical Rating Scale of Anxiety (NRSA) and 0-10 Pain Rating Scale. The results showed that the intervention was able to reduce anxiety and pain in patients with AMI (p 0.05).